(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Dementia is one of the significant health issues among the elderly1. It is the fifth leading cause of death and the primary cause of disability and dependence in older adults[2]. Hypertension, particularly in the elderly, is associated with an increased risk of memory impairment and dementia. Although numerous epidemiological studies demonstrate a relationship between hypertension and dementia, there remains considerable debate regarding the connection between these two conditions. Objective: To investigate the prevalence of depression in elderly patients with chronic coronary artery disease and identify the related factors influencing this condition. Methods: A descriptive cross-sectional study. All elderly patients diagnosed with chronic coronary syndrome at the Cardiology Department of Thong Nhat Hospital from November 2023 to August 2024. Results: Among 185 eligible patients in the department, depression risk was screened using the GDS-15 scale. The prevalence of depression in elderly patients undergoing treatment for chronic coronary syndrome at the Cardiology Department of Thong Nhat Hospital was 13.51%, with mild, moderate, and severe levels accounting for 9.73%, 2.7%, and 1.08%, respectively. Nutritional status was an independent factor associated with depressive disorders, where patients at risk of malnutrition or suffering from malnutrition had an increased risk of depression. Conclusion: The prevalence of depression in the study population remains high, and with the reported association, assessing the nutritional status of hospitalized patients with chronic coronary syndrome is essential. This assessment holds significance not only for intervention but also for screening the risk of depression in these patients.